(untitled) (Global Journal of Medical Research, 2017)
The aim of the study was to identify the demand side factors that determine the decision to utilize maternal care from medically qualified providers in the rural village of Bangladesh. Different scholarly articles have divided the problem of health services into two categories of factors: demand side factors and supply side factors. In this study, we are considering only the demand side factors only because the supply has increased substantially over time. The study was conducted in Udaypur Aruakandi village of Bagerhat distrct where the government health care facility (UHC) is only 1 km away. Econometric methods are used to identify demand side determinants of health service utilization in general. Data from 60 selected women who has given birth within 2.5 years or were pregnant at the time of data collection from three strata of households from a purposively chosen village of Bangladesh were collected in the period 25 December, 2015 to 5 January, 2016. This study used both qualitative and quantitative analyses to identify the factors that affect the use of maternal health care. In the study area out of the 60 women, 53% received antenatal care from a medically trained provider, making 4 ANC visits is only by 30% women, 49% of the delivery were attended by SBAs, 35% of the women received post natal care from medically qualified providers. So the utilization of maternal care is very low. The result of logistic regression analysis show that in general the likelihood of using maternal care services is affected by the socio-economic conditions, family education, occupation and age of the respondent individually. The level of family education was found to be the main factor associated with use of the MCH services, besides, perception of quality about the services provided by nearest health care facilities, wantedness of pregnancy, women’s decision making power are also the important determinants of maternal care utilization from medically qualified sources.